2016
DOI: 10.1002/chem.201604414
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkylation of Alkenes by Frustrated Lewis Pairs

Abstract: The activation of perfluoroalkyl iodides by the frustrated Lewis pair tris(pentafluorophenyl)borane and tri-tert-butylphosphine is described. By abstraction of both a fluorine and an iodine atom, an iodophosphonium fluoroborate salt is formed. In the presence of alkenes the corresponding iodoperfluoroalkylation products are generated regioselectively. First mechanistic investigations support a radical mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 118 publications
1
28
0
Order By: Relevance
“…In our studies addressing the Lewis-base-mediated iodoperfluoroalkylation of simple alkenes [40,42,43] we found that catalytic amounts of phosphines and phosphites effectively catalyze this process with complete regioselectivity upon irradiation with visible light (461 nm) (Scheme 1). Mechanistic investigations involving 19 F-NMR analysis suggested the intermediate formation of an EDA complex F(CF 2 ) n -I • • • PR 3 by halogen bond formation to the phosphorus atom [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…In our studies addressing the Lewis-base-mediated iodoperfluoroalkylation of simple alkenes [40,42,43] we found that catalytic amounts of phosphines and phosphites effectively catalyze this process with complete regioselectivity upon irradiation with visible light (461 nm) (Scheme 1). Mechanistic investigations involving 19 F-NMR analysis suggested the intermediate formation of an EDA complex F(CF 2 ) n -I • • • PR 3 by halogen bond formation to the phosphorus atom [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Alkenes play a ubiquitous role in the realm of chemical synthesis due to their enriched reactivity and abundance, fluoroalkylation of carbon-carbon double bonds is an attractive method for accessing fluorine containing compounds. Since 1945, atom transfer radical addition (ATRA) has extensively been utilized for fluoroalkylation of alkenes [20][21][22][23][24][25][26][27][28][29]. However, the preparation of alkenes containing fluorinated functional groups via Heck-type reaction were less studied owning to the lack of efficient and general strategies [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal complexes 11 (based on ruthenium, iridium, copper) or organic dyes 12 (eosin Y, rose bengal, riboflavin) are nowadays popular catalysts for photochemical reactions. 9a,13 In 2016, we reported the frustrated Lewis pair (FLP)catalyzed iodoperfluoroalkylation of unsaturated hydrocarbons, 14 which was followed by further mechanistic studies in 2019 (Scheme 1). 15 For these transformations, we used the popular FLP consisting of tris(pentafluorophenyl)borane (2) (often abbreviated as BCF) and tri-tert-butylphosphine (1).…”
mentioning
confidence: 99%
“…(1) (10 mol%) and B(C 6 F 5 ) 3 (2) (10 mol%) as catalysts 14,15 As this FLP-mediated iodoperfluoroalkylation showed some peculiar characteristics, we investigated the mechanism of this reaction more thoroughly. 15 While activation of the iodoperfluoroalkane by the Lewis base was indicated by NMR spectroscopy, kinetic studies revealed strong evidence for an additional photomediated process.…”
mentioning
confidence: 99%
See 1 more Smart Citation